Selection of nursing course subjects offered in the distance modality (Research, Society and Development, 2022)
In this study we analyze a selection of subjects offered at a distance in a nursing course. Course and distance learning coordinators, national distance education and nursing course manager were interviewed. The speeches of the course coordinators diverge in relation to the selection of subjects to be offered in the distance modality – one claims to be unaware and the other indicates involvement of the collegiate and the structuring nucleus of teachers, information corroborated by the national manager, who claims to also consider other health courses. The national distance learning manager affirms that the selection is made by “trial and error” based on the need and a reduction of each discipline through demands and evaluations made by students and teachers. Regarding the transposition of the presential to the distance modality, they claim to have no knowledge of how it works and that the materials are common to both modalities. In the project of the course there are no criteria for the selection of subjects to be offered in the distance modality. The insertion of technologies in higher education institutions is an inevitable movement and increasingly present in the daily life and it is up to the teaching teachers to contribute to this mediation.